Residências secundárias: as fontes estatísticas e a questão conceitual - Tulik, Olga (Revista Turismo em Análise, 1995)
This is a theoretical analysis of secondary residences as private tourism housing, used temporarily during leisure time by people who live elsewhere. Trough the approach brought by the specific literature, statistical sources are related with conceptual questions to arrive at the comprehension of the tem in Brazil.